Gender Disparity in Civic Engagement among Former Offenders in the U.S. Population - Mahmood, Senik T. (American journal of criminal justice, 2014)
The study examines gender disparities in civic engagement: volunteering, religious affiliation, and other group membership (such as social clubs, recreational groups, trade unions, commercial groups, professional organizations, or groups concerned with children like the PTA or boy scouts) as reflected in the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC) - Waves 1 and 2 datasets collected in years 2001–2002 and 2004–2005. This comparison was conducted with special focus on female former offenders. After controlling for socio-demographic and mental health variables, adjusted odds ratios indicated that female former offenders were at increased likelihood to be civically disengaged than their male counterparts. Policy implications of study findings involving females offenders are discussed.